Cross-Functional Project Groups in Research and New Product Development: Diversity, Communications, Job Stress, and Outcomes - Keller, Robert T. (Academy of Management Journal, 2001)
A model of cross-functional project groups was developed and hypotheses were tested in a study of 93 research and new product development groups from four companies. The results showed that functional diversity had indirect effects through external communication on one-year-later measures. Technical quality and schedule and budget performance improved, but group cohesiveness diminished. Functional diversity also had an indirect effect through job stress on group cohesiveness, which was again reduced. Implications for the development of conceptual models of cross-functional groups and their effective management are discussed.